Uso do misoprostol retal para indução do parto em gestantes com amniorrexe prematura : ensaio clínio fase II - Arcanjo, Francisco Carlos Nogueira (2005)
To investigate whether rectally administered misoprostol is an effective method for induction of labor in patients with ruptured membranes at term. Methods: A trial was conducted, enrolling 70 women with alive, singleton cephalic fetus and ruptured membranes between 37 and 41 weeks of pregnancy, with Bishop score less than 6 and without evidence of labor. They received rectal misoprostol (50mcg) every 4 hours until active labor was diagnosed. Outcomes included time from induction to labor and induction to delivery, incidence of tachysystole, mode of delivery, incidence of chorioamnionitis and neonatal outcome. Results: The mean (±SD) induction-to-Iabor and induction-to-delivery interval were 286.5 ± 154.6 minutes and 661.4 ± 290.4 minutes, respectively. The frequency of tachysystole was 11.4%. 77.1% of patients achieved vaginal delivery. Chorioamnionitis was diagnosed in 8.6% of patients. Median Apgar score at 1st and 5th minutes were 8 and 9 respectively. There was one case of Apgar < 7 at 5st minute. Neonatal sepsis occurred in 10% of neonates. Conclusions: Induction of labor with rectal misoprostol in the setting of premature rupture of membranes was effective, with 77.1% of vaginal deliveries and a low rate of chorioamnionitis. These findings must be confirmed in large randomized controlled trials.